Evaluation of the long-term behavior of potential plutonium waste forms in a geological repository. Issue 1665 (2014) - Deissmann, Guido; Neumeier, Stefan; Brandt, Felix; Modolo, Giuseppe; Bosbach, Dirk
ABSTRACT: Various candidate waste matrices such as nuclear waste glasses, ceramic waste forms and low-specification "storage" MOX have been considered within the current UK geological disposal program for the immobilization of separated civilian plutonium, in the case this material is declared as waste. A review and evaluation of the long-term performance of potential plutonium waste forms in a deep geological repository showed that (i) the current knowledge base on the behavior and durability of plutonium waste forms under post-closure conditions is relatively limited compared to HLW-glasses from reprocessing and spent nuclear fuels, and (ii) the relevant processes and factors that govern plutonium waste form corrosion, radionuclide release and total systems behavior in the repository environment are not yet fully understood in detail on a molecular level. Bounding values for the corrosion rates of potential plutonium waste forms under repository conditions were derived from available experimental data and analogue evidence, taking into account that the current UK disposal program is in a generic stage, i.e. no preferred host rock type or disposal concept has yet been selected. The derived expected corrosion rates for potential plutonium waste forms under conditions relevant for a UK geological disposal facility are in the range of 10 -4 to 10 -2 g m -2 d -1 and 10 -5 to 10 -4 g m -2 d -1 for borosilicate glasses, and generic ceramic waste forms, respectively, and ∼5·10 -6 g m -2 d -1 for storage MOX. More realistic assessments of the long-term behavior of the waste forms under post-closure conditions would require additional systematic studies regarding the corrosion and leaching behavior under more realistic post-closure conditions, to explore the safety margins of the various potential waste forms and to build confidence in long-term safety assessments for geological disposal.